Vilniaus miesto centro urbanistinės-architektūrinės ir paveldosaugos problemos - Glemža, Jonas (Journal of Architecture and Urbanism, 2011)
Urban–architectural and heritage conservation problems in Vilnius city centreHistoric parts of the city, Old Town, New Town, and the new buildings on Gedimino and Konstitucijos avenues form the city centre of Vilnius. These parts are situated on the opposite banks of the River Neris. The above mentioned avenues are the main streets and the river is the spatial axis of the centre. In the process of development of Vilnius city centre, the principal problems should be solved: 1. to further preserve cultural heritage; 2. to use a stable expansion in the development; 3. to strengthen the architecture and singularity of its natural surroundings in the city centre. Specific suggestions are presented for the development or regeneration of separate building spaces in the streets of the city centre relating them to the Official Plan of Vilnius (from 2007 to 2015).Article in Lithuanian.Santrauka. Vilniaus miesto centrą sudaro istorinės miesto dalys – Senamiestis, Naujamiestis su naujais statiniais Gedimino ir Konstitucijos prospektuose, kurie yra skirtingose Neries upės pusėse. Šie prospektai yra pagrindinės gatvės, o upė – erdvinė centro ašis. Vystant Vilniaus centrą turėtų būti sprendžiamos trys pagrindinės problemos: 1) tolesnis kultūros paveldo, jo vietovių saugojimas; 2) taikoma tvari plėtra vystant centrą; 3) architektūrinės bei gamtinės centro aplinkos savitumo stiprinimas. Teikiami konkretūs vertinimai bei siūlymai dėl atskirų centro gatvių užstatymo vietų vystymo ar gaivinimo, siejant tai su Vilniaus miesto Bendruoju planu iki 2015 metų ir jo įgyvendinimu.Reikšminiai žodžiai: Vilniaus miesto centras; miesto vystymas, regeneravimas; urbanistinė paveldo vietovė.First Publish Online: 22 May 2013